Risks for Children on the Internet: The “Brain Rot” Phenomenon - Vinarova, Milena (Media and Language, 2025)
The transformations that high technologies offer us today generate many questions about the existence and development of humanity in the future. As a top priority for any society, children are exposed to risks not only due to unequal social status, but also due to the lightning-fast entry of artificial intelligence into our lives. The article aims to open the door to another reading of the risks in young people – not physical and social inequalities, but the undermining of the child’s mental development, caused by the strong influence of the virtual network. The results reinforce our opinion that the excessive stay of children in front of screens suggests the development of the now-famous term “brain rot”.
Keywords: brain rot; screen media activity; children; risks; safety